Correlation between Physical Activity and Erectile Dysfunction at Office Workers in Grogol Subdistrict, Sukoharjo - Gabriella Diandra Nurbianto; Mujosemedi .; Bhisma Murti (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2014)
Backgrounds: Erectile dysfunction is the persistent inability to attain and maintain an erection sufficient to permit satisfactory sexual performance. Although it is a benign disorder, erectile dysfunction may affect physical and psychosocial health and may have a significant impact on the quality of life of sufferers and their partners. Physical activity is a protective factor for normal erectile function. Objection of this research is to know correlation between physical activity and erectile dysfunction at Office Workers in Grogol Subdistrict, Sukoharjo. Methods: This research was an observational analytic research in cross sectional study that has been done at Grogol Subdistrict, Sukoharjo on May-June 2014. The study was conducted on 40 men aged 30-50 years old, have been married for more than 2 years, have at least 1 child, in good income and economic condition, having graduated from junior high school, as permanent office worker, and passed the screening Lie-scale Minnesota Multiphasic Personality Inventory (LMMPI). In addition, they were not smokers, having no history of chronic disease, and or abnormalities of the genitals. Data collected by questionnaires and were analyzed with Chi Square test as well as Multiple Logistic Regression Analysis. Results: Twenty five out of forty subjects had high physical activity, 21 subjects out of them had no erectile dysfunction, in contrast, the other 4 subjects had. The rest of fifteen subjects of the others had low physical activity. Five subjects out of them had no erectile dysfunction, in contrast, 10 subjects out of the others had. It means that erectile dysfunction was more often presented in subject that had low physical activity than subjects that had high physical activity. Multiple Logistic Regression Analysis showed the value of p=0.049 and odds ratio=0.19. Conclusions: There is significant correlation between physical activity and erectile dysfunction at office workers in Grogol Subdistrict, Sukoharjo. High physical activity can reduce the risk of erectile dysfunction Keywords: Erectile dysfunction, physical activity, stress, office worker